2010
DOI: 10.1536/ihj.51.111
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure Response to Exercise as a Predictor of Mortality in Patients With Chronic Heart Failure

Abstract: SummaryIt is well known that peak oxygen consumption and heart rate (HR) recovery after exercise obtained from the cardiopulmonary exercise test are prognostic parameters in patients with chronic heart failure (CHF). However, it is unclear whether exercise-induced parameters obtained from the routine exercise stress test predict mortality in patients with CHF.We studied 136 patients (93 males/43 females) with CHF. All patients underwent symptom-limited exercise stress testing. Exercise parameters included exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…During ET, in patients with altered washout rate (state of adrenergic hypertonia at rest), we found that SBP at peak exercise and the number of METs showed lower values when compared The variation in SBP during exercise is directly associatedwith cardiac output during exercise: a lower increase in intrastress SBP may result from inotropic deficit during the exercise, which is a common phenomenon in patients with ventricular dysfunction, and this finding is associated with a worse prognosis 2 . Fargard et al 22 in a sample of patients eligible for heart transplantation, demonstrated that an inadequate variation in SBP in response to submaximal exercise is a predictor of cardiac events.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…During ET, in patients with altered washout rate (state of adrenergic hypertonia at rest), we found that SBP at peak exercise and the number of METs showed lower values when compared The variation in SBP during exercise is directly associatedwith cardiac output during exercise: a lower increase in intrastress SBP may result from inotropic deficit during the exercise, which is a common phenomenon in patients with ventricular dysfunction, and this finding is associated with a worse prognosis 2 . Fargard et al 22 in a sample of patients eligible for heart transplantation, demonstrated that an inadequate variation in SBP in response to submaximal exercise is a predictor of cardiac events.…”
Section: Discussionmentioning
confidence: 79%
“…Some of the parameters used in ET are the behavior of systolic blood pressure (SBP) intrastress and chronotropic reserve, which are recognized predictors of prognosis [2][3][4] . The adrenergic hyperactivity, a characteristic of HF, may lead to chronotropic incompetence, decrease in cardiac contractile response to catecholamines and decreased sympathetic reserve during exercise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As most of these patients received fl uids prior to study enrollment, we hypothesized that rates of fl uid responsiveness would be , 25% and that additional fl uid administration would not lead to durable improvements in hemodynamic parameters. Since the ability to increase cardiac output aft er a fl uid bolus might indicate a more adaptable cardiovascular system, and cardiovascular adaptability has been linked to improved outcomes in other conditions, [11][12][13] we also hypothesized that clinical outcomes would be better in patients who were fl uid responsive.…”
mentioning
confidence: 99%